Entrevista investigativa videograbada a niños, niñas y adolescentes víctimas de delitos sexuales : fundamentos y orientaciones técnicas basadas en evidencia internacional (Ediciones Universidad Católica de Chile, 2016)
This book describes the benefits of implementing videotaped investigative interviews in criminal proceedings. Based on the experience of almost a decade of the Fundación Amparo y Justicia, in the analysis of international studies and practices in the matter, the characteristics of this methodology, its foundations, its technique and the considerations for its correct application are detailed. This work will allow operators and authorities of the Justice System, students, academics, technical advisors and professionals from different fields, to find clear answers about a procedure that must be fully understood to guarantee its successful implementation in Chile.